Narrative-Based Intervention and Emotional Intelligence in Female Children - Ghafaryan Shirazi, Yasaman; Punamäki, Raija-Leena; Peltonen, Kirsi; Malekzadeh, Mohammad; Esmaeili , Ozra (East European Journal of Psycholinguistics, 2021)
Children share their emotional experiences through narratives, and high-quality narratives are beneficial for their wellbeing and development. This research investigated whether narrative-based interventions in the school context can increase children's emotional intelligence (EI). It tested three intervention settings' effect in their oral and written narrative elements: 1) oral co-narration, 2) literary narrative, and 3) Merging co-narrating and literary narrative. The sample consisted of 91 female Iranian students (age = 12±.21), who were selected randomly to these three intervention groups where they received a two-month training and one control conditions with treatment as usual. The Emotional Quotient inventory, the youth version (EQ-i: yv) test, was used to measure the students' EI levels before and after the intervention. The results demonstrated that oral and written narrative have different effects on student’s EI. The results revealed a significant increase in the EI score among children who participated in the oral co-narrating group and merged co-narrating and literary narrative intervention group. In contrast, the literary narrative intervention was not effective enough to increase children's EI. In conclusion, oral and written language modes and their merged narrative elements are crucial when tailoring effective school-based interventions to impact students' EI with language minority. Educators need to apply the oral and written narrative elements in their instructional design of the EI interventions considering the narrative style of students. In particular, oral language as the developmentally and socio-culturally appropriate tool can involve student's more with making sense of text and thereby support the learning process in EI interventions.
Keywords: emotional intelligence; oral language and literacy; perspective-taking; empathy; school-based intervention; Iranian female children